Forms and functions of nonverbal communication in native and non-native French lecturers’ classrooms - Rohali, Rohali; Tobing, Roswita Lumban; Rahayu, Siti Perdi; Zuleika, Tika (LITERA, 2026)
This study explores the categories and pedagogic functions of nonverbal communication used by native-speaker and non-native-speaker French teachers teaching French as a Foreign Language (FLE). This study used descriptive qualitative method through room-talk analysis to be observed in Yogyakarta State University. There were two non-native lecturers, a man and a woman, the participants. The data were collected from non-participating classes by means of observations, field notes, and audio-visual recordings. The discussion was limited to the following are nine forms of nonverbal communications: body language, facial expressions, eye contact, posture, proxemics, silence, touch, paralanguage, visual-aids and demonstrations. The results argue that these nine lecture delivery modes are key pedagogic resources through which lecturers shape meaning-making, manage class interaction, and develop lecturer-student relational intimacy. The non-native lecturer displays an increased desire for instruction clarity manifested in a more controlled body language, strategically employed silences, and minimized paralanguage. Conversely, the native speaker prefers interactional dynamism, readily employing hand gestures, spatial dynamics, engaging friendly facial expressions and a variety of paralanguage signals. Overall, the findings highlight the importance of nonverbal communication and its role in the co-construction of a multimodal, interactional-based pedagogic context in teaching French at university. Eye contact, posture, touch and visual illustrations are other communicative resources that help to reinforce the dynamics of the classroom interactions.